The ecophysiology of cape gooseberry (Physalis peruviana L.) - an Andean fruit crop. A review - Fischer, Gerhard; Melgarejo, Luz Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
In a literature review of the ecophysiology of cape gooseberry (Physalis peruviana L.) it was found that in Colombia this typical Andean plant adapts to a wide altitudinal range of the tropical cold climate, between 1,800 and 2,800 m a.s.l., with optimal medium temperatures between 13 and 16°C and base (minimum) temperatures for stem and fruit growth of 6.3 and 1.9°C, respectively. However, this fruit does not withstand temperatures <0°C. The Andean conditions of the tropics such as high solar radiation and rather short day lengths <12 hours favor flower initiation. A duration of 1,500-2,000 hours year-1 of direct sunshine are the most favorable for the size, quality and ripening of the fruit. Under field conditions in Bogota we measured a photosynthesis rate of A = 10.545 μmol CO2 m-2 s-1 and light compensation point Ic = 13.645 μmol photons m-2 s-1. As this species with an indeterminate growth habit requires a constant supply of water, while high amounts or heavy rains after a dry season cause cracking of the fruits, the plant does not tolerate waterlogging for more than 4 days. Cape gooseberry is classified as moderately tolerant to salinity and 30 mM NaCl curiously promotes growth, since the plant has mechanisms such as increased antioxidant activity to protect against saline conditions.